Bioavailability Of Phosphorus And Its Effect On The Nutrient Utilization In Cattle (Bangladesh Journal of Animal Science, 2012)
Eighteen indigenous growing cattle of two years old having initial live weight of 100 ± 4.5 kg were used to investigate the bioavailability of phosphorus from different sources (Di-calcium phosphate, Bone meal, Sesame oil cake, Mustard oil cake and Poultry liter) and its effect on the nutrient utilization and phosphorus balance of cattle. The animals were divided into 6 groups having 3 animals in each to one of group and randomly allocated into six diets in a Completely Randomized Design (CRD). Six dietary treatments are : T0 (control diet), T1 (Control + DCP), T2 (Control + Bone meal), T3 (Control+ mustard oil cake), T4 (Control+ sesame oil cake) and T5 (Control + poultry litter). The controlled diet contained 0.20% P and DCP, Bone meal, mustard oil cake, sesame oil cake and poultry litter were added to diets T1, T2, T3, T4 and T5, respectively to elevate the dietary P level of 0.45% for meet up the deficiency. The lowest daily DM intake (g/d) was observed in animals fed on diet T0 and the highest value was recorded for diet T5 and significantly (P0.05) higher for dietary groups T2, T3 and T5 (74.50) than T0 (62.16), T1 (73.15) and T4 (70.16%). The true absorption of P for supplemented diets (T1, T2, T3 and T5) was numerically higher than the diet T0, and T4. P balance was significantly (P